Outing Class sebagai Strategi Pembelajaran Kontekstual dalam Implementasi Kurikulum Merdeka pada Muatan IPAS Kelas III SD: Penelitian Kualitatif - Rachma maharani; Endah Yunita; Husnul Khatimah; Azzura Salsabilla; Urip Urip Sulistiyo; Syahrial; Muhammad Sofwan; Destrinelli (STKIP Subang, 2025)
Outing Class learning is a contextual learning strategy that allows students to gain hands-on learning experiences in a real-world environment. This type of learning is highly relevant within the Independent Curriculum (Curriculum Merdeka), emphasizing flexibility, hands-on experience, and the development of the Pancasila Student Profile. This study aims to describe how Outing Class is implemented as a contextual learning strategy in third-grade elementary school science (IPAS) content and to identify the benefits, challenges, and strategies used by teachers. The study used descriptive qualitative methods using observation, interviews, and documentation. The results indicate that Outing Class increases student motivation, participation, and conceptual understanding, but faces challenges such as safety risks and managing student behavior. Teachers address these challenges through briefings, group division, intensive supervision, and parental involvement. Outing Class learning is effectively implemented within the Independent Curriculum when supported by thorough planning and sound risk management.